Pelatihan Memanfaatkan Teknologi Internet Untuk Pembelajaran Anak Usia Dini - Harman, Rika; Amrizal; Darmansah; Arnomo , Sasa Ani (PUAN INDONESIA, 2024)
Currently, the world of information and communication technology is developing rapidly. There are many platforms and facilities available so that people can use the media whenever they want. Information technology has entered various fields, such as offices, education, arts, and many more. In the field of education, technology can be used in various ways, from creating learning media, learning processes, to presenting lesson material. we just need to choose which technology to use. However, new problems arise for many teachers because they cannot utilize this learning media. Because they continue to use traditional and old approaches to create learning media, the resulting material will be uninteresting and seem boring. Plus, today's students are more focused on what they see. If there is a special attraction, students will learn more. This training aims to educate PAUD teachers on how to use the internet as a learning resource for their students. The material that will be presented can be in the form of recognizing letters, recognizing numbers, recognizing animals, recognizing plants and much more. The results of this training provide new knowledge to PAUD teachers to create teaching materials quickly and easily using various platforms that can be accessed using the internet network. Then Improve the quality of teaching—ECD teachers who gain knowledge and skills through this training have the ability to improve the quality of their teaching, develop innovative learning strategies, and create more interesting and interactive learning experiences for children.